2019
DOI: 10.1021/acs.inorgchem.9b02245
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Polyamidoamine Design To Increase Uptake and Efficacy of Ruthenium Complexes for Photodynamic Therapy

Abstract: In this work, we report the synthesis of [Ru(phen) 3 2+ ]based complexes and their use as photosensitizers for photodynamic therapy (PDT), a treatment of pathological conditions based on the photoactivation of bioactive compounds, which are not harmful in the absence of light irradiation. Of these complexes, Ru-PhenISA and Ru-PhenAN are polymer conjugates containing less than 5%, (on a molar basis), photoactive units. Their performance is compared with that of a small [Ru(phen) 3 2+ ] compound, [Ru(phen) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 71 publications
0
32
0
Order By: Relevance
“…We have recently reported on the synthesis as well as the chemical and photophysical characterization of a linear polycationic PAA complexed with a luminescent tris-phenanthroline Ru complex, called Ru–PhenAN ( Chart 1 ), which is at the basis of this investigation. 36 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently reported on the synthesis as well as the chemical and photophysical characterization of a linear polycationic PAA complexed with a luminescent tris-phenanthroline Ru complex, called Ru–PhenAN ( Chart 1 ), which is at the basis of this investigation. 36 …”
Section: Results and Discussionmentioning
confidence: 99%
“…Reactions with longer times at lower temperature allow producing smaller polymers (by SEC analysis M n = 11,912, M w = 13,577, polydispersity index = 1.14), with respect to the one obtained previously. 36 The polymer is characterized by two mean p K a values (p K a1 = 3.35, p K a2 = 7.40) that make the polymer cationic below a pH value of 7.40, and instead only slightly positive (about 25% of the repeating units) at physiological pH. 36 Polycationic polymers have been shown to promote endosomal escape and it is known that their overall charge and buffering capacity are at the basis of endosomal escape mechanisms promoted by the so-called proton sponge effect, 38 even though other theories and mechanisms of escape by cationic species have been proposed in the literature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…They then decided to vary the structure of PAMAM by synthesizing Ru8‐PhenAN with a M n value of 34 600, M w / M n of 1.38 and 2% of Ru‐containing repeating units that could self‐assemble into ≈10 nm nanoparticles. [ 36 ] The PDT efficiency of Ru8‐PhenAN was evaluated in HeLa cells and compared to that of Ru8‐PhenISA and [Ru(phen) 2 (BAP)](OTf) 2 ( Ru9 ), a complex used as a model of the photoactive units. Ru8‐PhenAN was found to be more cytotoxic than Ru8‐PhenISA and Ru9 in HeLa cells with an EC 50 of 0.7 × 10 −6 m as opposed to 9 × 10 −6 m for the free complex upon visible light irradiation (40 min, 23.7 mW cm −2 ).…”
Section: Organic Nanoparticlesmentioning
confidence: 99%
“…62 As examples, selenium [63][64][65] , silver 66 , gold [67][68][69] and silicon [70][71][72][73][74] nanoparticles as well as upconverting nanoparticles [75][76][77] were successfully loaded with Ru(II) polypyridine complexes, forming a drug delivery vehicle. Further, the physical encapsulation of Ru(II) polypyridine complexes into polymeric partciles [78][79][80][81][82][83][84][85][86] , micelles [87][88][89] , dendrimers 90 or liposomes [91][92] was reported. Recent studies have also shown the conjugation of Ru(II) polypyridine complexes to carbon nanotubes [93][94][95] as well as metal-organic frameworks 96-97 as a delivery system.…”
Section: Introductionmentioning
confidence: 99%